2021
DOI: 10.1007/s11104-021-05217-z
|View full text |Cite
|
Sign up to set email alerts
|

Stockpiling disrupts the biological integrity of topsoil for ecological restoration

Abstract: Purpose Biotic and abiotic properties of soils can hinder or facilitate ecological restoration, and management practices that impact edaphic factors can strongly influence plant growth and restoration outcomes. Salvaged topsoil is an invaluable resource for mine-site restoration, and a common practice is topsoil transfer from mined areas to restoration sites. However, direct transfer is often not feasible, necessitating storage in stockpiles. We evaluated the effects of topsoil stockpiling on pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…These findings are further supported by previous studies using the same bioassay species, Acacia saligna , to evaluate effects of topsoil stockpiling on plant growth and root symbionts. A study using the same topsoils as used here assessed plant growth, physiology, and nodulation by nitrogen‐fixing bacteria (Valliere et al 2021) and recorded minimal differences in soil physiochemistry in stockpiled versus native reference topsoils, suggesting negative effects of topsoil stockpiling on plant performance were biotic in nature. Further, Valliere et al (2021) observed less root nodulation (lower rhizobial activity) in A. saligna seedlings grown in stockpiled topsoils than reference topsoils, which is in line with the Gorzelak et al's (2020) finding that key rhizobia taxa were lacking in stockpiled topsoils when compared to fresh topsoils.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…These findings are further supported by previous studies using the same bioassay species, Acacia saligna , to evaluate effects of topsoil stockpiling on plant growth and root symbionts. A study using the same topsoils as used here assessed plant growth, physiology, and nodulation by nitrogen‐fixing bacteria (Valliere et al 2021) and recorded minimal differences in soil physiochemistry in stockpiled versus native reference topsoils, suggesting negative effects of topsoil stockpiling on plant performance were biotic in nature. Further, Valliere et al (2021) observed less root nodulation (lower rhizobial activity) in A. saligna seedlings grown in stockpiled topsoils than reference topsoils, which is in line with the Gorzelak et al's (2020) finding that key rhizobia taxa were lacking in stockpiled topsoils when compared to fresh topsoils.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, soil physiochemistry showed few and minor differences between native soils and stockpiles (Table S2; Valliere et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations